2010
DOI: 10.1002/jrs.2816
|View full text |Cite
|
Sign up to set email alerts
|

UV‐resonance Raman micro‐spectroscopy to assess residual chromophores in cellulosic pulps

Abstract: Ultraviolet-resonance Raman (UV-RR) micro-spectroscopy is an appropriate and sensitive tool to assess the chromophore structures in bleached cellulosic pulps used for papermaking. The particular selectivity in detection and identification of chromophores in pulps is achieved by acquiring the UV-RR spectra in the solid state with laser excitation at 325 nm. This wavelength corresponds to absorption of poly-unsaturated chromophore structures in partially bleached/fully bleached pulps, and linearly correlated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Loureiro et al . used UVRR microspectroscopy to assess residual chromophores in cellulosic pulps . By monitoring pulp bleaching by UVRR, they found that it is the formation of polysaccharide‐derived chromophores upon bleaching that affects brightness of bleached pulps.…”
Section: Biosciencesmentioning
confidence: 88%
“…Loureiro et al . used UVRR microspectroscopy to assess residual chromophores in cellulosic pulps . By monitoring pulp bleaching by UVRR, they found that it is the formation of polysaccharide‐derived chromophores upon bleaching that affects brightness of bleached pulps.…”
Section: Biosciencesmentioning
confidence: 88%
“…A particular selectivity in the detection and identification of chromophores in pulps is achieved with UV-RR at 325 nm laser beam excitation. This band at 325 nm in the DR spectra corresponds to the absorption of polyunsaturated chromophore structures (Loureiro et al 2011 ).…”
Section: Uv-rr Spectroscopymentioning
confidence: 99%
“…Loureiro et al (2010Loureiro et al ( , 2011 showed by UV-RR coupled to UV-vis diffuse reflectance (DR) spectroscopy that xylan is an important source of chromophores in bleached eucalypt pulps. A particular selectivity in the detection and identification of chromophores in pulps is achieved with UV-RR at 325 nm laser beam excitation.…”
Section: Uv-rr Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations